Biomass allocation between reproductive and vegetative organs of Artemisia along a large environmental gradient - Tumenjargal Tsogtsaikhan; Xuejun Yang; Ruiru Gao; Jiangrui Liu; Wenqiang Tang; Guofang Liu; Xuehua Ye; Zhenying Huang (BMC Plant Biology)
Abstract Background Biomass allocation reflects functional tradeoffs among plant organs and thus represents life history strategies. However, little is known about the patterns and drivers of biomass allocation between reproductive and vegetative organs along large environmental gradients. Here, we examined how environmental gradients affect biomass and the allocation between reproductive and vegetative organs. We also tested whether the allocation patterns conform optimal or allometric partitioning theory. Methods We collected 22 Artemisia species along a large environmental gradient in China and measured reproductive (infructescences including seeds) and vegetative (leaves, stems and roots) mass for each plant. We then used standardized major axes regressions to quantify the relationships between reproductive and vegetative organs and linear mixed-effect models to examine the effect of environmental gradients (climate and soil) on biomass allocation patterns. Results We found significant negative correlations between total biomass of Artemisia and the first principal component of climate, an axis that was negatively correlated with temperature and precipitation. Overall, there were significant isometric relationships between reproductive and vegetative mass. In addition, the ratio of reproductive to vegetative mass increased with the second principal component of climate (representing climate variability), but decreased with the second principal component of soil (representing bulk density and available water capacity). These patterns were consistent at the individual and interspecific levels, but were mixed at the intraspecific level. Conclusions Our findings of the plastic responses of biomass allocation to environmental gradients support the optimal partitioning theory (OPT). The isometric relationships between reproductive and vegetative organs indicate that plant growth and reproduction are intricately linked. Furthermore, the plasticity of biomass ratios of reproductive to vegetative organs to climate variability and soil physical properties suggests that the flexible allocation between growth and reproduction is crucial for successful adaptation to diverse habitats.